Threshold sensitivity of taste perception and the role of saliva and Zinc level in some physiological & pathological conditions - Zaidan, Taghreed F.; Al-Omary, Wasan M.; Al-Sandook, Tahani A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Decreased taste acuity to the four basic tastes is closely related to health problems (diseases & medications), aging, and smoking. This study aimed to determine taste detection and recognition thresholds to the four basic tastes in some physiological and pathological conditions, determine saliva flow rate, serum and saliva zinc levels in these groups.Objective and Methods: The study includes 218 individuals (35–80) years old divided into six groups; the control, aging (subjects over 60 years), smokers, diabetics, haemodialysis patients and hypertensive patients on chronic use of captopril.The taste detection and recognition thresholds of sweet, salty, sour and bitter tastes, saliva flow rate were determined. Zinc concentration was assessed in serum and saliva spectrophotometricaly.Results: The results showed a significant increase in the taste detection and recognition thresholds of the four basic tastes of all groups than in the control, except the salty taste thresholds of the haemodialysis group and the salty taste detection threshold of the diabetics. Saliva flow rates, serum and saliva zinc levels decreased significantly at p